Spin-capable carbon nanotube sheet as a substitute for TCO in transparent electronics and displays. Issue 5 (3rd May 2016) - Hwang, Young-Ha; Han, Maeum; Lim, Jinho; Lee, Gil S.; Jung, Daewoong
ABSTRACT: Spin-capable carbon nanotubes (CNTs) are proposed as a promising material for transparent conductive films (TCFs) to replace indium tin oxide (ITO) in optoelectronic and flexible applications. CNT-TCFs were prepared by a dry-spun method, a straightforward transfer process for fabricating CNT-based films. The effects of acid treatment on the electrical and optical properties of CNT-TCF were evaluated. After acid treatment, the CNT-TCF possesses a much higher electrical conductivity and slightly improved transparency compared to films that have not undergone acid treatment. The electrical properties of the CNT films were dramatically affected by the type of acid treatment. The CNT-TCF treated with a fuming acid treatment exhibited better performance than the CNT-TCF treated with immersion acid treatment only, with a low sheet resistance (210 Ω/sq) and high transmittance (90%) comparable to those of ITO films.